Global Supply Chains and Economic Interdependencies: A Literature Study - Andri Irawan (Yayasan Vifada Cendikia Indonesia, 2023)
This study investigates the influence of global supply chain configuration on economic dependence in an increasingly globally connected world. This study uses a qualitative research design with a literature analysis method to combine insights from supply chain management, international economics, and resilience studies. The findings of this study show that integrating digital technology in supply chains increases resilience. However, there are still challenges in managing the impact of supply chain disruptions on regional and global economic dependencies. The implications of this research include recommendations for developing sustainable supply chains, adjusting trade policies, and improving resilience strategies in the face of supply chain disruptions. This research contributes by bringing together theory and practical application to understanding how supply chain configuration affects economic outcomes in the era of globalization.